Enhanced Self‐Powered UV Photoresponse of Ferroelectric PZT Materials by Pyroelectric Effect. Issue 12 (10th October 2017) - Song, Kai; Ma, Nan; Yang, Ya
Abstract: Semiconductor materials based UV photodetectors can be operated via photovoltaic effect by converting UV light into electric signals. Recent studies have been focused on how to fabricate excellent semiconductor materials based photodetectors through construction of heterojunctions, which may not be suitable for practical large‐scale devices due to the high cost and sophisticated fabrication process. Here, by utilizing naturally existing temperature change of UV illumination and the pyroelectric effect of ferroelectric materials, a novel self‐powered UV photodetector based on Pb(Zr, Ti)O3 (PZT) material is presented through a simple fabricating process, which can be well utilized to detect 365 nm UV light by using light‐induced temperature variation. Under a temperature change rate of 2.40 K s −1, the voltage response and the corresponding responsivity can be enhanced by larger than 6600% as compared with that of individual UV light illumination. This study provides a feasible solution to realize self‐powered UV light detection by utilizing light‐induced pyroelectric effect in PZT. Abstract : A self‐powered UV photodetector by utilizing the light‐induced pyroelectric effect in Pb(Zr, Ti)O3 (PZT) is designed for realizing the 365 nm UV detection. By applying external heating, both the voltage response and the corresponding responsivity can be largely enhanced as compared with that of individual UV light illumination.